Attenuation of Conductance in Cobalt Extended Metal Atom Chains - Georgiev, V; Sameera, W; McGrady, J (2012)
Density functional theory, in conjunction with nonequilibrium Green's functions, is used to explore the attenuation of the resistance of Co x wires along the series Co 3(dpa) 4(NCS) 2, Co 5(tpda) 4(NCS) 2, and Co 7(teptra) 4(NCS) 2. At very low bias (0 < V < 25 mV) the conductance, G, decreases in the order G(Co 3) > G(Co 5) > G(Co 7), consistent with experiment and with an anticipated inverse relationship between conductance and chain length. At higher voltages, however, the current-voltage responses of all three are striking nonlinear, and above 50 mV G(Co 5) > G(Co 3) > G(Co 7). The very different behavior of the members of this homologous series can be traced to the different symmetries and multiplicities of their respective ground states, which in turn control the properties of the dominant transport channels. © 2012 American Chemical Society.